Aggressive osseous commitment result by keratocyst odontogenic tumour: case report, radiographic and clinical standpoints - Cardoso, Gerusa O. M. [UNESP]; Matta-Neto, Edgard [UNESP]; El Achkar, Vivian N. R. [UNESP]; Niccoli-Filho, Walter [UNESP] (Published by Oxford University Press and JSCR Publishing Ltd. All rights reserved. © The Author 2013., 2013)
Keratocystic odontogenic tumour (KCOT) previously known as odontogenic keratocyst was recently classified as a benign lesion characterized by an infiltrating pattern, local aggressiveness with the propensity to recurrence. It is thought to arise from the dental lamina. Pain is usually not associated with KCOT until swelling occurs, and it commonly affects the posterior mandible. Multiple KCOT are associated with nevoid basal cell carcinoma syndrome. This study reports an aggressive case of KCOT with destruction of the osseous tissue of the mandible, accentuated face asymmetry, dysphagia and dysphonia. It was managed with a defined protocol which entailed diagnosis, treatment with enucleation along with peripheral ostectomy and rehabilitation. A long-term follow-up schedule was provided to the patient to observe the recurrence behaviour of this cyst. In postoperative phase, no complication was noticed regarding wound healing and recurrence.